2016
DOI: 10.1111/jpi.12318
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of melatonin in experimental optic neuritis in rats

Abstract: Optic neuritis (ON) is an inflammatory, demyelinating, and neurodegenerative condition of the optic nerve, which might induce permanent vision loss. Currently, there are no effective therapies for this disorder. We have developed an experimental model of primary ON in rats through a single microinjection of 4.5 μg of bacterial lipopolysaccharide (LPS) into the optic nerve. Since melatonin acts as a pleiotropic therapeutic agent in various neurodegenerative diseases, we analyzed the effect of melatonin on LPS-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 62 publications
1
37
1
Order By: Relevance
“…The mechanism might be preventing the decrease in visual evoked potentials (VEPs) and pupil light reflex (PLR), inhibiting microglial reactivity, astrocytosis, demyelination, and axon and retinal ganglion cell loss and preserving anterograde transport of cholera toxin β-subunit from the retina to the superior colliculus. In the same study, the therapeutical effects of melatonin on ON was also observed as it reversed the decrease in VEPs and PLR completely when the pellet was implanted at 4 days postinjection of LPS [299]. …”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…The mechanism might be preventing the decrease in visual evoked potentials (VEPs) and pupil light reflex (PLR), inhibiting microglial reactivity, astrocytosis, demyelination, and axon and retinal ganglion cell loss and preserving anterograde transport of cholera toxin β-subunit from the retina to the superior colliculus. In the same study, the therapeutical effects of melatonin on ON was also observed as it reversed the decrease in VEPs and PLR completely when the pellet was implanted at 4 days postinjection of LPS [299]. …”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…Besides, more and more studies had focused on the therapeutic effect for ophthalmic diseases. Some showed that melatonin played a neuroprotective role in glaucoma patients, animal models of retinitis pigmentosa and optic neuritis . It is also suggested to possess antioxidant properties and decrease the level of prostaglandins in experimental feline uveitis .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, and in experimental models of optic neuritis and retinal ischemia, melatonin treatment inhibits glial reactivity and reduces the expression of hypoxia inducible factor ‐1α, COX‐2, and TNF‐α genes (Figure ) . It is, thereby, also acting as a neuroprotective agent.…”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 99%